Identifikasi Dampak Perkembangan Pariwisata Terhadap Lingkungan Fisik Di Pantai Kedonganan, Kecamatan Kuta Selatan, Kabupaten Badung, Bali - Betricks, Carolline Ellen; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2024)
This study aims to identify the impact of tourism development on the physical environment in Kedonganan Beach, South Kuta District, Badung Regency, Bali. As for this preparation, it is explained how tourism development uses the Tourism Area Life Cycle theory as reference and also its impact on the physical environment at Kedonganan Beach which focuses on its infrastructure. This study uses primary data taken from direct observation, interviews with informants and also literature studies. The data analysis used is descriptive-qualitative data analysis. The resulting conclusion is that the development of Kedonganan Beach tourism is at the engagement stage. The impact of tourism development on the physical environment of Kedonganan Beach consists of the positive and negative impacts of tourism development including the main facilities, complementary facilities, and tourism supporting facilities. Meanwhile, tourism infrastructure consists of public infrastructure and the needs of many people. Keywords: Impact, Tourism Development, Physical Environment